A study on fiber metal laminates by using a new damage model for composite layer. (October 2017) - Kashfi, M.; Majzoobi, G.H.; Bonora, N.; Iannitti, G.; Ruggiero, A.; Khademi, E.
Highlights: A simple nonlinear damage model is introduced to modify the linear elastic model of GFRE to nonlinear elastic behavior. The damage model parameters have been determined by iterative simulation and GA. VOCE relation has been considered to describe the flow curve of Al 2024 and the model constants have been calculated by optimization. A simple tensile tests have been carried out to verify the tensile behavior of the FML. The results of the proposed model showed a reasonable agreement with the experiments. Abstract: Fiber metal laminates (FMLs) are new hybrid materials which are widely used in aircraft industry due to their higher mechanical properties compared to monolithic metal and epoxy based composites. In this work, mechanical behavior of the FML is investigated by experiment and simulation. The FML used in this study is made of two layers of aluminum 2024 and a layer of glass-fiber reinforced epoxy (GFRE). The experiments showed nonlinear elastic behavior for GFRE layer. This behavior is due to damage evolution and material degradation. Therefore, a simple nonlinear damage is presented to improve the results of the proposed material model. Mechanical properties of the layers are measured by uniaxial tensile test. Numerical simulations are performed by implementing the material model into the user subroutine of MSC MARC FE code. The results of the proposed model showed a reasonable agreement with the experiments. The agreement confirms the nonlinear damage behavior of the FMLs observed in the experiments. Graphical abstract: